TEORIA E PRÁTICA: PARADIGMA FOCAL DO PROFISSIONAL DE EDUCAÇÃO FÍSICA (Fiep Bulletin - online, 2024)
Taking Inclusive Education as a reference, the adapted student and their representation in the job market. With the aim of analyzing the languages of the adapted student as a place of speech and their place of speech in Brazilian society. Philosophy as a place of speech in relation to contribution from the perspective of those who qualify for the job market. The stages of the research were argued systematically by Literature Review in narrative format, because with regard to the peculiarity, supposedly, installed in society regarding people with disabilities, presumably, the stages converge towards ignorance. In this way, Theory and Practice: Focal Paradigm of the Physical Education Professional presents the problem of how to identify the adapted student with a place of speech in the contemporary paradigms of those who practice physical exercise. Highlighting the adapted student with Dissociative Disorders in the face of crises in Brazilian society. Thus, the languages of the adapted student who studies. It is increasingly necessary to use in practice what is learned in theory, and not just have a theory to justify the practice in a disconnected way.